Landmarks in Humanities - K. Fiero Gloria (Mc Graw-Hill, 2005)
LANDMARKS in Humanities is a single-volume survey of global culture designed for students of humanities, cultural history, and history of the arts. In chronological sequence, LANDMARKS highlights the most notable monuments of the human imagination--those works of art and architecture, literature, philosophy, and music that have been foremost in shaping the world's cultures.